2000
DOI: 10.1523/jneurosci.20-23-08659.2000
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in Endogenous Opioid Peptides in the Rat Medullo-Coerulear Pathway after Chronic Morphine Treatment

Abstract: Several biochemical changes have been described in noradrenergic neurons of the locus coeruleus (LC) after chronic morphine treatment. Changes in neurochemical expression in opioid afferent projections to the LC may be equally important in modulating noradrenergic neurons during chronic opiate exposure. To test the hypothesis that opioid peptides in LC afferents are altered after chronic opiate administration, we exposed adult male rats to either morphine or placebo pellets for 5 d. Tissue sections through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Decreased expression following chronic morphine was also described in other brain areas, like the HPT (PVN, 149), FrCx, (26), medulla oblongata (MO), and nucleus paragigantocellularis (PGi; Ref. 384). However, increased levels of Penk mRNA were detected in the HPC (26), whole cortex, and spinal cord (145).…”
Section: Modifications Of Opioid System Gene Expression Under Chromentioning
confidence: 83%
“…Decreased expression following chronic morphine was also described in other brain areas, like the HPT (PVN, 149), FrCx, (26), medulla oblongata (MO), and nucleus paragigantocellularis (PGi; Ref. 384). However, increased levels of Penk mRNA were detected in the HPC (26), whole cortex, and spinal cord (145).…”
Section: Modifications Of Opioid System Gene Expression Under Chromentioning
confidence: 83%
“…For Western blot analysis, rat brains were sectioned and the DRN removed by punch dissection using a 2-mm trephine (Biomedical Research Instruments, Rockville, MD, USA). Protein was extracted in RIPA buffer with added soybean trypsin (25 μg/ml) and benzamidine (0.1 mM) as described previously (Van Bockstaele et al, 2000). Protein levels were quantified, 25 μg protein/lane was separated in a 4-20% Tris-glycine gel (Bio-Rad Laboratories, Hercules, CA, USA) and transferred to Immobilon-P membrane (Millipore, Bedford, MA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Thus, increases or decreases in enkephalin immunoreactivity were reported to occur in brain tissues after chronic treatment with morphine, whereas in other studies, no change was observed (Van Bockstaele et al, 2000). These differences are very likely attributable to the following: (1) the various experimental protocols used in chronic opioid treatment and the regioselectivity of the effects (Tejwani and Rattan, 1997); and (2) the use of different techniques to measure the enkephalin levels, such as autoradiography , in situ hybridization (Lightman and Young, 1987;Tjon et al, 1997), or peptide extraction from tissues (Tejwani and Rattan, 1997).…”
Section: Abstract: Enkephalin; Cholecystokinin; Microdialysis; Rewarmentioning
confidence: 77%